2004
DOI: 10.1016/j.tem.2004.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Galanin-like peptide as a link in the integration of metabolism and reproduction

Abstract: The arcuate nucleus is a hypothalamic center that couples energetics and reproduction. Peptide-releasing neurons in the arcuate nucleus receive and process humoral signals from the periphery and relay this information to other nuclei in the hypothalamus and preoptic area. Galanin-like peptide (GALP) is expressed in the arcuate nucleus, and GALP-containing neurons are targets for the action of leptin. GALP-containing neurons are closely apposed to gonadotropin-releasing hormone (GnRH) neurons in the preoptic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 74 publications
(101 reference statements)
0
44
0
3
Order By: Relevance
“…However, those hormonal studies were carried out before cloning and/or characterization of key molecular signals in the integrated control of metabolism and reproductive function, such as leptin, GALP (galanin-like peptide), and, more recently, kisspeptin (2,35,39). Such recent developments force us to accommodate these new factors into the previously known hypoganodotropic phenotype of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…However, those hormonal studies were carried out before cloning and/or characterization of key molecular signals in the integrated control of metabolism and reproductive function, such as leptin, GALP (galanin-like peptide), and, more recently, kisspeptin (2,35,39). Such recent developments force us to accommodate these new factors into the previously known hypoganodotropic phenotype of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…GALPpositive neurons appear to be directly stimulated by leptin as they possess the ObRb leptin receptor. It has been demonstrated that central administration of GALP stimulates GnRH release and subsequently LH secretion in numerous mammalian models (Gottsch et al, 2004b;Kauffman et al, 2005b). GALP expression, as one would expect by its leptin/insulin control, is profoundly reduced by implementation of CR regimes.…”
Section: Galanin-like Peptide (Galp)mentioning
confidence: 99%
“…GALP reduces food intake and body weight to the same degree in GALR1-and GALR2-deficient mice when compared with wild-type mice, 30 and GALR2-deficient mice do not show abnormal feeding behavior. 15 Furthermore, the GALR2/3 agonist (AR-M1896) has no effect on feeding or body weight in either the rat or the mouse. 19 Therefore, more studies are required to determine the receptor mediating the anorectic actions of GALP but, as this peptide can act differently in rodents when compared with galanin, a new/unidentified GALP-specific receptor is likely to be involved.…”
Section: Galp and Its Receptorsmentioning
confidence: 99%
“…12 To date, GALP has been shown to act as an agonist at all three galanin receptor subtypes in vitro, although it shows preference for GALR2 and GALR3, as compared with GALR1. 7,13 There is a considerable body of evidence linking GALP to the regulation of food intake, energy metabolism and reproduction, [13][14][15][16][17][18][19] as well as fluid intake. 20,21 Furthermore, recent reports have suggested that GALP has a role in conditions such as epilepsy, Alzheimer's disease 22 and diabetes, [22][23][24] in addition to serving a vasoactive function.…”
Section: Introductionmentioning
confidence: 99%